2023
DOI: 10.1186/s12936-023-04487-5
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the prevalence of dihydropteroate synthase-431V mutation and other sulfadoxine-pyrimethamine resistance markers in Plasmodium falciparum isolates in Nigeria

Abstract: Background Malaria is a major public health issue with substantial risks among vulnerable populations. Currently, the World Health Organization (WHO) recommends SP-IPTp in the second and third trimesters. However, the efficacy of SP-IPTp is threatened by the emergence of sulfadoxine-pyrimethamine resistant malaria parasites due to single nucleotide polymorphisms in the Plasmodium falciparum dihydrofolate reductase and dihydropteroate synthetase genes. This study aimed to assess the current prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The Pfdhfr mutant alleles N51I, C59R, and S108N have been found to be highly prevalent and widespread in Africa, as well as the triple mutant Pfdhfr I 51 R 59 N 108 haplotype. Almost all had a prevalence of over 90% 17,[24][25][26][27] . Previous research also showed the mutant Pfdhfr I164L had a high frequency in Asia, with relatively low prevalence in Africa [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…The Pfdhfr mutant alleles N51I, C59R, and S108N have been found to be highly prevalent and widespread in Africa, as well as the triple mutant Pfdhfr I 51 R 59 N 108 haplotype. Almost all had a prevalence of over 90% 17,[24][25][26][27] . Previous research also showed the mutant Pfdhfr I164L had a high frequency in Asia, with relatively low prevalence in Africa [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%